2003
DOI: 10.1103/physrevb.67.184415
|View full text |Cite
|
Sign up to set email alerts
|

CoFe stripes: Magnetization reversal study by polarized neutron scattering and magneto-optical Kerr effect

Abstract: We have studied the magnetization reversal of a laterally structured film with both, magneto-optical Kerr effect and with polarized neutron scattering in the off-specular regime. The lateral structure consists of 90-nm thick and 1.2-m wide Co 0.7 Fe 0.3 stripes with a grating period of 3 m. Magnetization reversals were measured for different orientations of the sample with respect to the field directions. In addition, Kerr microscopy was used for visualizing the domain state. Due to the high aspect ratio of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…In H ? case, reversal occurs much smoother indicating dominant coherent rotation of spins with partial domain nucleation at H c [18].…”
Section: Article In Pressmentioning
confidence: 93%
See 1 more Smart Citation
“…In H ? case, reversal occurs much smoother indicating dominant coherent rotation of spins with partial domain nucleation at H c [18].…”
Section: Article In Pressmentioning
confidence: 93%
“…4, the elongate shape of stripes favors breaking of the in-plane isotropic distribution of anisotropy axis, that leads domain magnetization directions to reorient closer to the stripe length. However, a strong uniaxial anisotropy along stripe direction is still not established, as expected in narrower Co 50 Fe 50 stripes [18], since a typical hard axis hysteresis loop is not observed when H ? .…”
Section: Article In Pressmentioning
confidence: 96%
“…For these experiments, the attention was focussed on the off-specular reflectivity, which shows intense satellite peaks due to the in-plane periodicity of the dot array. It was previously demonstrated that off-specular PNR can reveal in-plane structures and that the spin-analyzed intensity of a satellite peak as function of the applied field allows to monitor the magnetization reversal process [17][18][19][20]. The specular reflectivity is largely dominated by the nonmagnetic Si substrate, and, therefore, does not contribute any information about the magnetic state of the bars.…”
Section: Article In Pressmentioning
confidence: 97%
“…This method has provided invaluable information on exchange coupling [4,5], on exchange bias [6][7][8][9][10][11][12], and on the complex magnetism of ultrathin films [13][14][15]. Most recently, it has been demonstrated that neutron scattering can also be used for studying the re-magnetization process of patterned magnetic structures [16][17][18][19][20]. From polarized neutron scattering, information from the specular as well as from Bragg reflections of a periodic pattern can be obtained at small angles.…”
Section: Introductionmentioning
confidence: 96%